Pregnancy in dark winters: implications for fetal bone growth?. (18th April 2012) - Walsh, JM; Kilbane, M; McGowan, C; McKenna, MJ; McAuliffe, FM
Abstract : Background: Fetal bone development is entirely dependent on the maternal pool of calcium; as such there are concerns about inadequate vitamin D status in pregnancy. We sought to examine the prevalence of hypovitaminosis D in pregnancy and to correlate maternal vitamin D status to fetal anthropometry and birthweight. Study design: Sixty pregnant women had serum 25-hydroxyvitamin D (25OHD) measured in the early pregnancy, at 28 weeks and in cord blood. Two subgroups were analysed to examine results in the context of seasonal variation in 25OHD: a winter and a summer cohort. Fetal anthropometry was assessed with ultrasound at 20 and 34 weeks and at delivery neonatal anthropometry recorded. Results: There was a high prevalence of hypovitaminosis D ranging from 33% to 97%, with a marked seasonal variation. Maternal 25OHD correlated with fetal 25OHD in cord blood (p<0.05). Overall, fetal 25OHD concentrations correlated with biometry at 20 weeks gestation (head circumference, r=0.39, p=0.002; biparietal diameter, r=0.34, p=0.008; abdominal circumference, r=0.34, p=0.009; and femur length, r=0.35, p=0.008). In the winter cohort, a correlation was found between early pregnancy 25OHD and femur length at 20 weeks (r=0.34, p=0.07) and between maternal 28-week 25OHD (r=0.43, p=0.02) and femur length at 34 weeks. Additionally, mean infant length at birth was significantly shorter in those with an early pregnancy 25OHD concentration less than the median in early pregnancy. (52.1 vs. 53.6cm, p=0.04). Conclusion: In conclusion, the prevalence of maternal hypovitaminosis D is particularly high in women who are pregnant during winter months in northern latitudes. This may have potential detrimental effects on fetal skeletal growth.